2021
DOI: 10.1186/s12889-021-12316-0
|View full text |Cite
|
Sign up to set email alerts
|

Contested solidarity and vulnerability in social media-based public responses to COVID-19 policies of mobility restrictions in Singapore: a qualitative analysis of temporal evolution

Abstract: Background Mobility restriction is the most effective measure to control the spread of infectious disease at its early stage, especially if a cure and vaccine are not available. When control of the coronavirus disease 2019 (COVID-19) required strong precautionary measures, lockdowns were necessarily implemented in countries around the globe. Public health risk communication about the justification and scope of a lockdown was challenging as it involved a conflict between solidarity and individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Other studies also revealed a positive effect of fear of COVID-19 on stress and a prolonged exposure to stress would result in burnout ( 56 58 ). In line with other studies, we found the expected positive associations of the COVID-19 BVS with the presence of chronic illnesses ( 50 ), support for “living with the COVID” policy, i.e., by reducing the social distancing measures ( 51 ). Congruent with the literature, we found expected negative association of COVID-19 with age ( 13 , 50 , 54 , 59 ), status of COVID-19 vaccination ( 53 ), and attitude toward “dynamic Zero COVID-19 strategy” ( 41 , 54 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies also revealed a positive effect of fear of COVID-19 on stress and a prolonged exposure to stress would result in burnout ( 56 58 ). In line with other studies, we found the expected positive associations of the COVID-19 BVS with the presence of chronic illnesses ( 50 ), support for “living with the COVID” policy, i.e., by reducing the social distancing measures ( 51 ). Congruent with the literature, we found expected negative association of COVID-19 with age ( 13 , 50 , 54 , 59 ), status of COVID-19 vaccination ( 53 ), and attitude toward “dynamic Zero COVID-19 strategy” ( 41 , 54 ).…”
Section: Discussionsupporting
confidence: 91%
“…Other construal-related scales, including age, presence of chronic illnesses, support for living with the COVID policy, status of COVID-19 vaccination, and attitude about dynamic Zero COVID-19 strategy were used to analyse the concurrent validity of the COVID-19 BVS. Based on the current research findings, we expected a positive relationship of COVID-19 BVS with (i) FCV-19S ( 49 ), (ii) presence of chronic illnesses ( 50 ), and (iii) support for living with the pandemic, i.e., by reducing the social distancing measures ( 51 ). Research shows that burnout level may influence people's inertia or inaction toward vaccination ( 52 ).…”
Section: Methodsmentioning
confidence: 81%
“…Consistent with the literature on COVID-19, the results of the study show the positive association of the COVID-19 BFS with the Fear of COVID-19 Scale (r = 0.131, p < 0.001) [70,71], chronic illness condition (r = 0.090, p < 0.001) [73], the intention to adopt "living with COVID" policy (r = 0.292, p < 0.001) by reducing the quarantine and social distancing rules [72] and being against the "dynamic Zero COVID-19 strategy" (r = 0.340, p < 0.001). As reported in previous studies [71,[73][74][75]79], the results showed a negative association of the scale with COVID-19 vaccination status (r = −0.149, p < 0.001), "Have your family members or close friends ever been infected with COVID-19?"…”
Section: Discussionmentioning
confidence: 83%
“…Participants were invited to respond on a scale from "Strongly Disagree" to "Strongly Agree" on a 5-point Likert scale. With reference to the recent literature on COVID-19, we anticipated that the COVID-19 BFS is positively associated with Fear of COVID-19 [70,71], and support for "living with COVID" policy by reducing the quarantine and social distancing rules [72]. We also expected the COVID-19 BFS to be positively correlated with chronic illness conditions [73].…”
Section: Phase 2: Validation Of the Scalementioning
confidence: 99%
“…People who are stuck in pandemic burnout may lead to lower levels of motivation, feelings of helplessness, loneliness, hopelessness, depersonalization, and reduced personal achievement (Haktanir et al, 2022). Lau et al (2022) examined the psychometric properties of COVID-19 Burnout Views Scale (BVS) with a large Hong Kong sample and found the expected positive associations of COVID-19 BVS with the presence of chronic illnesses (Hayat et al, 2022), support for "living with the COVID" policy, i.e., by reducing the social distancing measures (Ligo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%